Government Actions And The Minerals Industry (The National Institute for Occupational Safety and Health (NIOSH), 1981)
Tax for Toxic Waste Cleanup. - The Superfund Act of 1980 became effective April 1, and provides that producers of certain metals and chemical substances are to be taxed in order to fund toxic waste cleanup. Industry will provide 88% of the 5-year, $1.6 billion fund. The Environmental Protection Agency will administer the Act, but the Internal Revenue Service will be responsible for collection of the industry tax. Under the Act, nickel companies, for example, will be required to pay a tax of 0.225 cents per pound on pure nickel products produced or imported into the United States. Standard for Exposure to Lead. - The Occupational Safety and Health Administration (OSPA) has announced a stricter standard on the test of a worker's exposure to lead. Effective May 15, in all lead intensive occupations with the exception of those at primary and secondary lead smelters, a worker would have to be removed from his work station if the level of lead in his blood tests out at 60 micrograms of lead per 100 grams of blood, instead of the previous standard of 70 micrograms. In the case of primary and secondary lead smelters, the ruling has been stayed until June 1, 1981, to allow time for further study.